Guidelines for working with deaf athletes - Kordić Milena; Karić Jasmina (Fizička Kultura, 2022)
The work was created with the desire to familiarize experts from the world of sports with the phenomenon of deafness and the culture that has developed within it. Sports occupy a special place in the Deaf community and culture. For this reason, the importance of sports activities for the deaf was emphasized and attention was focused on the contribution of the deaf in the world of sports, which developed within the phenomenon of deafness. The social role of sport and its importance in the implementation of social inclusion were especially emphasized. The aim of the work is to analyze the available literature in the period from 2000-2022 to determine how developed the inclusive perspective of sports is in the context of social change, such as acculturation, and to offer concrete guidelines that would facilitate familiarity and, therefore, acceptance of the peculiarities and values of Deaf culture. The following search engines were used for the literature search: Ebscohost, ScienceDirect, Wiley Inter Science and SpringerLink, KoBSON, Google Scholar. The results obtained from the review of the literature indicate the importance of the role of sports coaches in creating a stimulating climate, as well as that sports provide great opportunities in leveling the differences that place deafness and Deaf culture in the context of handicaps. Specific guidelines are listed and described, which not only serve to introduce sports experts to the deaf, but also to enrich the work in the world of sports, which also leads to the essential realization of social inclusion.